Communicating Public Information Disclosure and E-government Strategy in Pamekasan - Zulaikha, Zulaikha; Susilo, Daniel; Mustofa, Amirul; Dizon, Carl C. G. (Nyimak: Journal of Communication, 2024)
E-government refers to utilizing information technology in public information services as a means of innovating government functions related to public services. The objective of this study is to examine and analyze the progress of e-government in the implementation of the public information disclosure initiative in the Pamekasan Regency. This study employs a qualitative methodology utilizing descriptive techniques. The study was carried out at the information and documentation management agency under the Local Government of Pamekasan in Indonesia. The findings in this study indicate that the progress of the e-government information management infrastructure and documentation has been satisfactory. The public can utilize this information service through their electronic devices, however, the accessibility remains inconsistent. The public service site has been consolidated with multiple affiliated entities. This research makes a valuable contribution to the existing body of knowledge and practical implementation of government information disclosure in public services. By focusing on contemporary data, this research offers a unique and distinctive perspective within the context of analysis.Keywords: E-government, information policy, information disclosure, public communicationABSTRAKE-government merujuk pada penggunaan teknologi informasi dalam layanan informasi publik sebagai cara untuk menginnovasikan fungsi pemerintah terkait dengan layanan publik. Tujuan dari penelitian ini adalah untuk mengevaluasi dan menganalisis kemajuan e-government dalam pelaksanaan inisiatif pengungkapan informasi publik di Kabupaten Pamekasan. Penelitian ini menggunakan metodologi kualitatif dengan menggunakan teknik deskriptif. Penelitian dilakukan di lembaga manajemen informasi dan dokumentasi di bawah Pemerintah Daerah Pamekasan, Indonesia. Temuan dalam penelitian ini menunjukkan bahwa kemajuan infrastruktur manajemen informasi dan dokumentasi e-government telah memuaskan. Masyarakat umum dapat memanfaatkan layanan informasi ini melalui perangkat elektronik mereka, namun, aksesibilitasnya masih tidak konsisten. Situs layanan publik telah dikonsolidasikan dengan beberapa entitas terafiliasi. Penelitian ini memberikan kontribusi berharga terhadap pengetahuan yang ada dan implementasi praktis pengungkapan informasi pemerintah dalam layanan publik. Dengan fokus pada data kontemporer, penelitian ini menawarkan perspektif yang unik dan khas dalam konteks analisis.Kata Kunci: E-government, kebijakan informasi, pengungkapan informasi, komunikasi publik